Attention restoration during environmental exposure via alpha-theta oscillations and synchronization. (April 2020) - Chen, Zheng; He, Yujia; Yu, Yuguo
Abstract: Evidence has revealed that exposure to a restorative environment can have health and cognitive benefits, but the mechanism remains unclear. This study was designed to explore the neural mechanism of environmental restorative experiences. We conducted an experiment by randomly exposing thirty-two participants to either 20 min of a restorative (wooded garden) or a nonrestorative (traffic island) environment. Participants' real-time electroencephalogram (EEG) signals were monitored via a 14-channel mobile device during the exposure. They also completed a series of psychological assessments of affective and cognitive functioning, as well as the perceived restorativeness of the environment, before and after the exposure. The results revealed stronger and more efficient alpha-theta synchronization (functional connectivity) during the restorative experience, as well as stronger alpha-theta oscillations in the occipital lobes. Regression analysis revealed that perceived coherence was associated with the efficiency of the alpha-theta synchronization network (alpha: coef. = 2.02, 95% CI [0.68, 3.36], p  = 0.020, R 2  = 23.97%; theta: coef. = 2.41, 95% CI [1.30, 3.52], p  < 0.001, R 2  = 39.54%); fatigue recovery was associated with alpha-theta oscillations in the occipital lobes (alpha: coef. = -0.58, 95% CI [-0.88, −0.28], p  = 0.001, R 2  = 33.62%; theta: coef. = -0.50, 95% CI [-0.73, −0.26], p  < 0.001, R 2  = 37.74%); and the degree of fatigue recovery further improved attention-related cognitive performance (coef. = 0.22, 95% CI [0.03, 0.41], p  = 0.027; R 2  = 15.28%). Based on the abovementioned evidence, we proposed that the perceived coherence of the restorative environment may induce fatigue recovery and, hence, attention restoration via alpha-theta oscillations and synchronization. The increased alpha-theta oscillations in the occipital lobes suppress visual processing, allowing the human brain to reorganize itself via alpha-theta synchronization. Highlights: Alpha-theta brain waves may play an important role in restoration. Restorative environments may induce occipital oscillations associated with fatigue recovery. Nonrestorative environments may induce inefficient synchronizations associated with incoherence.